UPAYA PEMBERDAYAAN KESEJAHTERAAN MASYARAKAT PEDESAAN DI KABUPATEN NGAWI MELALUI PROGRAM ONE VILLAGE ONE PRODUCT - Khoyrul Anwar (LPPM STISIP Persada Bunda, 2022)
The purpose of this study was to determine the efforts of the Ngawi Regency Government. empowering local community businesses through the implementation of the one village one product (OVOP) program. The research was conducted with a qualitative approach, with data collection techniques through in-depth interviews, observation, and secondary data analysis to obtain comprehensive information in finding data and facts to answer the main problems in this study. The researcher uses the theory of one village one product and the theory of regional development. The results showed that the one village one product program was able to develop community businesses, which was marked by an increase in the number of small and medium enterprises as many as 924 in the period 2015 to July 2020. Some of the leading commodities developed were the manufacture of teak wood handicrafts, durian fruit centers. and other creative food industries. Some of these superior products have proven to be able to survive and compete with domestic and foreign products, some of which have even been exported to various countries.